Global shifts in DNA methylation and DNA hydroxymethylation across multiple brain regions in transgenic models of tau and amyloid pathology: Molecular and cell biology/others. (7th December 2020) - Castanho, Isabel; Murray, Tracey K.; Harvey, Joshua; Leung, Szi Kay; Lunnon, Katie; Ahmed, Zeshan; Mill, Jonathan
Abstract: Background: There is increasing evidence to support a role for altered DNA modifications in Alzheimer's disease (AD). Global changes in both DNA methylation (5mC) and DNA hydroxymethylation (5hmC) have been robustly reported in cancer, but not widely studied in AD. We quantified global levels of 5mC and 5hmC across multiple brain regions in two transgenic models of AD pathology, relating these to the progressive changes in tau and amyloid observed in the same samples. Method: We investigated global DNA modification levels in brain tissue from rTg4510 and J20 mice using two independent approaches. We quantified hippocampal global DNA methylation in rTg4510 and J20 transgenic (TG) and wild‐type (WT) littermate control mice using an enzymatic‐based methylation assay combined with pyrosequencing. Using immunohistochemistry, we directly quantified levels of both 5‐methylcytosine (5mC) and 5‐hydroxymethylcytosine (5hmC) in multiple brain regions in rTg4510 and J20 mice. Result: We identified both genotype‐associated and progressive temporal changes (interaction between genotype and age) in 5mC and 5hmC in rTg4510 TG and J20 TG mice compared to WT littermate controls in several brain regions. Levels of both 5mC and 5hmc were negatively correlated with levels of tau and amyloid pathology, reflecting some evidence from human AD brain. Conclusion: We identified decreased levels of two DNA modifications (5mC and 5hmC) associated with accumulation of tau and amyloid pathology. Both genotype‐associated and progressive changes in 5mC and 5hmC measured by immunohistochemistry were observed, with these changes notably stronger in rTg4510 TG relatively to J20 TG mice, particularly in the hippocampus.